(untitled) - Ter Haar, G.

Laser powder bed fusion produced Ti-6AI-4V: microstructural transformations and changes in deformation behaviour through thermal treatments. (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.